The Self-Reflexive Tabletop Role-Playing Game - Evan Torner (G|A|M|E The Italian Journal of Game Studies, 2016)
Tabletop role-playing games combine performance, procedures, and improvisation to both tell stories and reflect on the nature of storytelling. This article discusses the three games 1,001 Nights by Meguey Baker, What Is a Role-Playing Game? by Epidiah Ravachol, and World Wide Wrestling by Nathan D. Paoletta in terms of how their procedures of play and framing devices comment on the tabletop role-playing game medium. Taken together, these three games on games demonstrate the inherent tensions of player motivation, collective fiction creation, and selling a performance to one’s fellow players, and how RPG theory helps us to understand them.